Unveiling Gambogenic Acid as a Promising Antitumor Compound: A Review - Mi, Li; Xing, Zhichao; Zhang, Yujie; He, Ting; Su, Anping; Wei, Tao; Li, Zhihui; Wu, Wenshuang (Planta Medica, 2024)
Gambogenic acid is a derivative of gambogic acid, a polyprenylated xanthone isolated from Garcinia hanburyi. Compared with the more widely studied gambogic acid, gambogenic acid has demonstrated advantages such as a more potent antitumor effect and less systemic toxicity than gambogic acid according to early investigations. Therefore, the present review summarizes the effectiveness and mechanisms of gambogenic acid in different cancers and highlights the mechanisms of action. In addition, drug delivery systems to improve the bioavailability of gambogenic acid and its pharmacokinetic profile are included. Gambogenic acid has been applied to treat a wide range of cancers, such as lung, liver, colorectal, breast, gastric, bladder, and prostate cancers. Gambogenic acid exerts its antitumor effects as a novel class of enhancer of zeste homolog 2 inhibitors. It prevents cancer cell proliferation by inducing apoptosis, ferroptosis, and necroptosis and controlling the cell cycle as well as autophagy. Gambogenic acid also hinders tumor cell invasion and metastasis by downregulating metastasis-related proteins. Moreover, gambogenic acid increases the sensitivity of cancer cells to chemotherapy and has shown effects on multidrug resistance in malignancy. This review adds insights for the prevention and treatment of cancers using gambogenic acid.
Keywords: gambogenic acid; Garcinia hanburyi; Guttiferae; antitumor activities; molecular mechanism; drug delivery systems